2012
DOI: 10.1136/jnnp-2011-301546
|View full text |Cite
|
Sign up to set email alerts
|

A new prevalence study of multiple sclerosis in Orkney, Shetland and Aberdeen city

Abstract: The prevalence of MS has increased in the overall area, most markedly in Orkney, then Shetland, over the past 30 years. This increase could be due to a number of factors, but rising incidence as reflected by a rising sex ratio, influenced by gene-environment interaction, is the most likely. Orkney has the highest prevalence rate recorded worldwide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 31 publications
2
30
0
Order By: Relevance
“…We found the nationwide point prevalence of MS in Iceland on December 31, 2007 to be 167 per 100,000 population for all cases, and 140 per 100,000 for CD-MS. Several population-based MS prevalence studies [2,5,[9][10][11][12][18][19][20] have been published in the last 2 decades (Table 2), with prevalence varying between studies. The differences may be partly due to the use of different inclusion criteria, and differences in healthcare among different countries.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We found the nationwide point prevalence of MS in Iceland on December 31, 2007 to be 167 per 100,000 population for all cases, and 140 per 100,000 for CD-MS. Several population-based MS prevalence studies [2,5,[9][10][11][12][18][19][20] have been published in the last 2 decades (Table 2), with prevalence varying between studies. The differences may be partly due to the use of different inclusion criteria, and differences in healthcare among different countries.…”
Section: Discussionmentioning
confidence: 99%
“…A 2009 population study from Scotland [10] reported a point prevalence of 238 per 100,000 (590 individuals; 70% women; population of 248,102). The study included all patients fulfilling Poser criteria for CD-MS (23), and 2.6: 1 in Canada [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There has been a general increase in disease prevalence in the last few decades that cannot be attributed to advances in neuroimaging or changes in diagnostic criteria [10]. Early authorities considered the incidence to be equal in females and males [11] but there is a slight female predominance in most prevalence studies [6].…”
Section: Epidemiology Of Msmentioning
confidence: 99%
“…In the last decades of the 20th century, the incidence of MS in females nearly doubled in many countries, while it has remained virtually unchanged for men. Studies designed to investigate change in MS sex ratio over time in different countries showed that this increase is more pronounced in areas located in the most northern latitudes [1][2][3] than in those in southern latitudes where a high sex ratio disequilibrium appears to be stable over time. 4 Inaccuracy of diagnosis and differences in ascertainment and study design might play a role in the geographical and temporal variations.…”
mentioning
confidence: 99%